2023
DOI: 10.1038/s41598-022-27153-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climatic environment on immunological features of rheumatoid arthritis

Abstract: The aim of this study was to clarify the effect of climatic environment on the immunological features of rheumatoid arthritis (RA). Blood samples were collected from patients with RA and healthy controls (HCs), matched by age and sex, living in two locations, Tsukuba and Karuizawa, which differ in their altitude and average air temperature and atmospheric pressure. Analysis of peripheral blood mononuclear cells (PBMCs) revealed that the proportion of T and B cell subpopulations in HCs and RA patients were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We found that most FRGs were differentially expressed between the ferroptosis clusters and that patients in cluster 1 had lower ferroptosis scores. Considering that immune disorder is the key feature of RA, there are abnormal levels of immune cells in blood and synovium in patients [ 30 ]. Therefore, we compared the infiltration of immune cells in the two clusters.…”
Section: Discussionmentioning
confidence: 99%
“…We found that most FRGs were differentially expressed between the ferroptosis clusters and that patients in cluster 1 had lower ferroptosis scores. Considering that immune disorder is the key feature of RA, there are abnormal levels of immune cells in blood and synovium in patients [ 30 ]. Therefore, we compared the infiltration of immune cells in the two clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that severe sun exposure is directly related to LN, although the mechanism has not been elucidated to date [ 44 ]. Similarly, studies about air pressure and rheumatic autoimmune diseases are increasing in recent years [ 45 , 46 ], but the clear role in LN needs further discussion as well.…”
Section: Discussionmentioning
confidence: 99%
“…This came with upregulation of Xylitol and L-pyroglutamic acid in the microbiome, underling the association between gut, environment and immune system (43). In addition, a recent, but arguably small, population study highlighted the possibility that climatic environment, such as air temperature and pressure, might have an effect on the proportion of T and B cell subpopulations, possibly triggering autoimmunity in RA (44). The potential link between seasonality and the activity of RA is a subject of increasing interest within the medical community, particularly concerning the role of vitamin D (45).…”
Section: Weather and Seasonalitymentioning
confidence: 99%